Risk factors of vitamin D deficiency and the effects of sunlight exposure and vitamin D supplementation on serum vitamin D level, adiponectin, cardiometabolic risk factors and metabolic syndrome among adults in Kelantan - Aris, Norliyana (2020)
In spite of abundant sunshine for cutaneous vitamin D (VD) synthesis, low levels of VD have been documented among Malaysian population. However, the effects of occupational sunlight exposure and monsoon seasons on VD are not well established. Besides, low VD levels has been associated with several non-bone or calcium-related outcomes including metabolic syndrome (MetS), which may mediated by adiponectin. This study was divided into two phases. Phase 1, a comparative crosssectional study was conducted to characterize the effect of occupational sunlight exposure and monsoon season on serum 25-hydroxyvitamin D (25(OH)D) and identify factors modifying the serum 25(OH)D levels. Besides, the relationship between 25(OH)D levels with high molecular weight (HMW) adiponectin and cardiometabolic risk factors were also observed. Phase 2, a quasi-experimental study was carried out for 12 weeks to evaluate the effects of moderate sunlight exposure (sunlight exposure group; 15 minutes sunlight exposure biweekly on face, arms, hands and feet; n=19), VD supplementation (VD supplement group, 50 000 IU cholecalciferol weekly, n=15] and placebo (placebo group, n=15) on serum 25(OH)D, HMW adiponectin and cardiometabolic risk factors in women with VD deficiency (serum 25(OH)D < 50 nmol/l). Both phases were carried out among Malay working adults in Kelantan from 2012 to 2015. Outcome measures comprises of anthropometric measurements (height, weight and waist circumference), body fat percentage and blood pressure assessment, fasting blood test (25(OH)D, HMW adiponectin, lipid profile, glucose, insulin and hs- CRP) and questionnaire (socio-demographic, medical history, sunlight exposure and sun protection use, physical activity assessment and VD intake). In phase 1, two-point data were collected in 138 outdoor and 143 indoor workers, first in non-monsoon (May-June 2012) and second in monsoon season (Jan-Feb 2013). Results of phase 1 study revealed that serum 25(OH)D levels were significantly higher in outdoor workers compared to indoor workers irrespective of season and sex (p<0.001). Furthermore, significant association between VD status and occupation was observed (p<0.001). Monsoonal differences of 25(OH)D was observed only in male outdoor workers (mean difference, MD = 10.39 nmol/l, p<0.001). However, in overall, no significant association was found between VD status and monsoon season (χ2(1)=0.076, p=0.783). Serum 25(OH)D level was directly predicted by hours of sunlight exposure (β=0.38, p=0.010) and inversely by sun protection score (β=-4.64, p=0.001), body mass index (β=-1.02, p=0.002), indoor occupation (β=-42.72, p<0.001) and female sex (β=-19.46, p<0.001). No significant relationship between VD with HMW adiponectin and cardiometabolic risk factors were found in this study (p>0.05). Considering the results of determinants of VD in Phase 1, female indoor workers with VD deficiency in both monsoon and non-monsoon seasons were recruited for phase 2 study. In phase 2, after 12 week of intervention, serum 25(OH)D increased significantly in sunlight exposure (MD = 14.27 nmol/l, p<0.001) and VD supplement group (MD = 14.30 nmol/l, p<0.001) but not in placebo group (MD = 1.63 nmol/l, p=0.067). Significant increase in HMW adiponectin was observed only in VD supplement group (MD=0.43 ng/ml, p=0.024). Among the MetS components, only glucose decreased significantly after 12 weeks of sunlight exposure (MD=-0.27 mmol/l, p<0.001) but no changes seen in the other groups. No significant changes were found in waist circumference, blood pressure, triglycerides and other cardiometabolic risk factors in all groups after 12 weeks. However, HDL-C was found increased significantly in all groups after the intervention (p<0.05). In conclusion, both moderate sunlight exposure and VD supplement interventions improved the VD levels, but the effects of VD on HMW adiponectin and cardiometabolic risk factors are still inconclusive.